Comparison of physical properties and effectiveness of facial wash gel nipah shell (Nypa fruticans Wurmb.) activated charcoal with palm shell (Elaeis guineensis Jacq.) activated charcoal as a facial cleanser - Uce Lestari; Eugenia Griselta; Muhaimin Muhaimin (Farmasains : Jurnal Farmasi dan Ilmu Kesehatan, 2021)
Activated charcoal is an amorphous carbon that has a high absorption capacity and can be made using plantation waste such as nipah shell and palm shell. Activated charcoal from nipah shell and palm shell have high absorption when used to absorb dirt and oil on the face by being formulated as a facial wash in the form of a gel. This study was conducted to compare the physical properties and effectiveness of facial wash gel with activated charcoal nipah shell and activated charcoal palm shell with a concentration of 4% of each activated charcoal and determine which facial wash gel has better physical properties and effectiveness than the control positive namely Biore Men Charcoal. The physical properties tested included: organoleptic observation, homogeneity, spreadability, pH, foaming ability, cycling test, irritation test, moisture and oil test using a skin analyzer and dirt absorption effectiveness test using a digital microscope. The results showed that facial wash gel activated charcoal palm shell had physical properties closer to control (+) and better effectiveness, with an average oil reduction percentage of 17% compared to facial wash gel activated charcoal nipah shell, which was 15%. From these results, it can be concluded that facial wash gel activated charcoal palm shell has better physical properties and is more effective in cleaning oil and dirt on the face compared to facial wash gel activated charcoal nipah shell.